DEVELOPMENT OF STUDENT WORKSHEET BASED ON TTW LEARNING MODEL TO IMPROVE STUDENT’S COMMUNICATION AND OBSERVATION SKILLS - Agustho Ayomi Tri Putra Agustho (Universitas Pancasakti Tegal, 2021)
This study aims to produce an appropriate of student worksheet based on TTW learning model to improve student’s communication and observation skills on environmental pollution matter nd to describe the effectiveness of the student worksheet based on TTW learning model to improve student’s communication and observation skills on environmental pollution matter. This study is a type of Research and Development (RnD) research with a 4D model which includes the steps of defining, designing, developing, and disseminating. The data analysis technique for the pretest and posttest scores of communication and observation skills is the paired sample t-test and the normalized gain score (n-gain score). The result show that developed student worksheet based on TTW learning model to improve students’ communication and observation skills about environmental pollution matter is appropriate to be use in science learning with “very feasible” by expert lecturers and students' response questionnaire. In addition, the results also show that the student worksheet based on TTW learning model is effective to improve communication and observation skills. The communication and observation skills of students improve significantly after using the student worksheet based on TTW learnig model. The improvement of studets’ communication and observation skills in the “medium” category with an N-gain score of 0,681.